Oral hygiene practice and oral health status of geriatric population in selected area of Rangpur, Bangladesh - Ahmad, Mohammad Sayeed; Mamun, Md Abdullah Al; Islam, Md Shahidul; Siddik, ANM Musa; Rahman, Md Zahedur; Asaduzzaman, HM (KYAMC Journal, 2018)
Background: Throughout the world, a demographic revolution is underway. The proportion of older people is growing faster than any other group. A growth spurt in the number of elderly persons has resulted from improvements in both social living conditions and medical care. This poses tremendous challenges to health and social policy planners, particularly because disease patterns will shift concurrently. Objectives: The present study was planned and carried out with the aim of assessment of the oral hygiene practice and oral health status among geriatric population. Materials & Methods: This cross sectional study was done among the geriatric population with a view to assess their oral hygiene practice and oral health status. Purposively selected 26 geriatric peoples were interviewed through a structured closed end questionnaire followed by a observational checklist. Results: In this study, it is found that most (84.6%) respondents brush their teeth regularly; more than half (57.7%) respondents brush their teeth twice; most (53.8%) of respondents brush their teeth after awake at morning, and 30.8% respondents brush 2-3 min; half of respondents use tooth brush and tooth paste. In this study, it is found that, respondents aged 70 years have Decayed Missed Filled Teeth (DMFT) (mean ± SD) 5.20 5.72, OHI (mean ± SD) 2.56 01.87. We also found that, respondents have Plaque Index (PI) (mean ± SD) 1.29 1.50, and GI (mean ± SD) 0.20 0.44. Conclusion: Oral health is one of the important components of aging; due to the presence of oral disease, it can affect general health and quality of life of elderly people. KYAMC Journal Vol. 9, No.-2, July 2018, Page 48-52